Optimizing Crystalline MoS2 Growth on Technologically Relevant Platinum Substrates Using Ionized Jet Deposition: Interface Interactions and Structural Insights - Cristian Tomasi Cebotari; Christos Gatsios; Andrea Pedrielli; Lucia Nasi; Francesca Rossi; Andrea Chiappini; Riccardo Ceccato; Roberto Verucchi; Marco V. Nardi; Melanie Timpel (Surfaces, 2025)
Transition metal dichalcogenides, especially molybdenum disulfide (MoS2), exhibit exceptional properties that make them suitable for a wide range of applications. However, the interaction between MoS2 and technologically relevant substrates, such as platinum (Pt) electrodes, can significantly influence its properties. This study investigates the growth and properties of MoS2 thin films on Pt substrates using ionized jet deposition, a versatile, low-cost vacuum deposition technique. We explore the effects of the roughness of Pt substrates and self-heating during deposition on the chemical composition, structure, and strain of MoS2 films. By optimizing the deposition system to achieve crystalline MoS2 at room temperature, we compare as-deposited and annealed films. The results reveal that as-deposited MoS2 films are initially amorphous and conform to the Pt substrate roughness, but crystalline growth is reached when the sample holder is sufficiently heated by the plasma. Further post-annealing at 270 °C enhances crystallinity and reduces sulfur-related defects. We also identify a change in the MoS2–Pt interface properties, with a reduction in Pt–S interactions after annealing. Our findings contribute to the understanding of MoS2 growth on Pt and provide insights for optimizing MoS2-based devices in catalysis and electronics.